Investigation of Methylammonium Tin Strontium Bromide Perovskite Systems. (1st January 2018) - Dimesso, L.; Mayer, T.; Jaegermann, W.
Abstract : The properties of methylammonium-tin-strontium bromide systems (CH3 NH3 Sn1-x Srx Br3, 0.0 ≤ x ≤ 0.1) were investigated. The X-ray diffraction analysis (XRD) revealed the presence of the untilted cubic Pm-3m perovskite and orthorhombic SnBr2 as major crystalline phases. The morphological analysis confirmed the XRD data by detecting the formation of polyhedral shaped crystallites attributed to MASnBr3 perovskite and elongated crystallites related to SnBr2 phase. Derivative differential thermal analysis (DDTA) and derivative thermogravimetric analysis (DTG) revealed a thermal stability of MASnBr3 phase till T = 250°C and showed the presence of more thermal events related to a multistep decomposition process. The addition of Sr-ions retained the cubic crystalline structure of the perovskite and enhanced its thermal stability at T = 150°C by reducing the weight loss rates. The optical spectra displayed values of absorption edges between 624 nm and 636 nm. The Tauc plots revealed a direct semiconducting behavior with band energy gaps at ∼2.02–2.03 eV. The emission photoluminescence (PL) spectra, measured at room temperature and excitation wavelength λexc = 380 nm as well as the excitation photoluminescence (PL) spectra, measured at room temperature and emission wavelength λem = 520 nm showed a dramatic increase of the intensity by adding the Sr-ions reaching a maximum for x = 0.025.